CAMPUR KODE DAN ALIH KODE DALAM PERCAKAPAN DI LINGKUP PERPUSTAKAAN UNIVERSITAS BENGKULU - Akhiri Laiman; Ngudining Rahayu; Catur Wulandari (Jurnal Korpus, 2018)
The purpose of this study is to describe the form of mixed code, the type of code transfer, the factors causing code interference, and the factors causing the transfer of code in the conversation in the library scope of University of Bengkulu. The method used in analyzing the data is descriptive qualitative method. Data collection technique in this research is done by documentation technique that is by recording conversation in library scope of University of Bengkulu and interviewing informant. The steps of analysis are done by stages: 1) Transcription data, 2) data identification, 3) data classification, 4) data reduction, 5) data analysis, 6) conclusion, and 7) data validation. The results of the analysis obtained in this research are: (1) the form of mixed code in the conversation in the library scope of Bengkulu University that occurs in the form of words, phrases, clauses, and tangible baster. (2) the type of code transfer in a conversation in the library scope of Bengkulu University that occurs on the type of internal code transfer and the type of external code transfer. As for (3) factors causing code interference due to: 1) language factor, 2) habit factor, 3) no exact expression factor in language being used, and 4) background factor of speaker's attitude. (4) factors that cause the transfer of code because: 1) factor adjusting the code used by the person, 2) third person presence factor, 3) speaker factor, 4) just prestigious factors, 5) the purpose factor to express something, and 6) factor indicates the first language. Keyword: mixed code, code transfer, conversation, library University of Bengkulu